The influence of visual impairment on separate indicators of a functional condition of touch systems of pupils of middle classes - Lydmyla Shesterova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to define and to compare separate indicators of a functional condition of touch systems of pupils of middle classes with visual impairment and their contemporaries with normal vision. Materials and Methods: pupils of middle classes with visual impairment and pupils of middle classes with normal vision took part in the research. During the research such methods were applied: analysis and synthesis of references, perimetry, determination of visual acuity by means of a special table, acumetry, esthesiometry, determination of resistance of a vestibular mechanism to rotary loadings, methods of mathematical statistics. Results: the analysis of separate indicators of a functional condition of visual, acoustical, vestibular and tactile analyzers of pupils with visual impairment and without them is carried out. Conclusions: it is established that the studied indicators of a functional condition of touch systems at pupils of middle classes with visual impairment are better, than at their contemporaries with normal vision